Biblioteczne rewolucje? transformacja przestrzeni i usług Biblioteki Publicznej w Świebodzinie = Library Revolutions? Transformation of Space and Services at the Public Library in Świebodzin - Kotlarek, Dawid (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
With the modernization of library infrastructure, it is equally important to adapt services to the contemporary needs of users. Modernizing space is only the first step ? the true transformation lies in the evolution of the library?s offers. A 21stcentury library should be not only a place to borrow books but also a centre for culture, education, and personal development. This means introducing modern tools, including those not immediately associated with traditional library activities.The Public Library in Świebodzin has been engaging in diverse activities for years, striving to meet the evolving needs of its users. Through space modernization and the introduction of innovative services, the facility has transformed into a modern centre for culture and education. The library now offers not only traditional book lending but also spaces for meetings, workshops, and educational activities such as programming workshops, themed club meetings, and stand-up comedy evenings.
Keywords: modernizacja; biblioteka; Świebodzin; przestrzeń; oferta; technologia; kultura; edukacja; modernization; library; space; offers; technology; culture; education